Recent progress in trivalent actinide and lanthanide solvent extraction and coordination chemistry with triazinylpyridine N donor ligands - Geist, Andreas; Panak, Petra (Solvent extraction and ion exchange, 2021)
A follow up to an earlier review on the coordination and extraction of trivalent actinide and lanthanide ions with triazinylpyridine N-donor ligands is presented. It reviews the recent development in the fields of ligand modifications and improvements, considering both hydrophobic compounds (to be used as extracting agents) and hydrophilic compounds (to be used as stripping agents), with a focus on fundamental studies.
Gesehen am 09.03.2021